EXPLORING THE RELATIONSHIP BETWEEN PREMIUM GROWTH, CLAIM EXPENSES, AND SOLVENCY: THE MEDIATING EFFECT OF PROFITABILITY - Erfan, Erfan; Indrabudiman, Amir (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This study aims to examine the effect of premium growth and claim expenses on solvency levels with profitability as an intervening variable. This research uses a quantitative approach using secondary data. The population in this study were 18 insurance companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The sample used amounted to 14 insurance companies (consisting of 70 data) obtained using purposive sampling method. The results showed that: (1) premium growth has no significant effect on profitability; (2) claim expense has no significant effect on profitability; (3) premium growth has no significant effect on solvency level; (4) claim expense has no significant effect on solvency level; (5) profitability has a negative and significant effect on solvency level; (6) profitability is not able to mediate the effect of premium growth on solvency level; (7) profitability is not able to mediate the effect of claim expense on solvency level.